EFEKTIVITAS PENGGUNAAN LEACHET HASIL PENGURAIAN SAMPAH DALAM PROSES BIODEGRADASI LIMBAH BATIK - Mulasari, Surahma asti (Jurnal Kesehatan Masyarakat (Journal of Public Health), 2012)
Background : Treatment of textile waste industry, including batik can be implemented with abiodegradation. Biodegradation by bacteria carried either aerobic or anaerob. The bacteria arewidely found in nature. On the other hand, the presence of bacteria in nature also function todecompose the waste. Own waste as a potential waste in the community. The use ofenvironmental biotechnology is possible to simultaneously address the environmental pollutioncaused by waste and garbage batik. The purpose of this study was to investigate to find out thedifference amount of in degrading microbial in leachet, the difference in content of organic C, N,and P in leachet as a nutrient for degrading microbial growth, the effectiveness of the useleachet biodegradation in the process of batik , and to determine the effectiveness of differentleachet in the biodegradation process of batik waste management.Methods : This was quantitative study with laboratory test to determine differences in theeffectiveness of the use of leachet.Results : The content contained microbs / bacteria so that the possibility of a biological processcan be implemented. There wave had of N, P, K nutrients in leachet for bacteria, waste pollutionparameters decreased but didnt significantly improve the quality of batik waste.Conclusion : There was no significant reduction the quality of batik waste.Key words : waste, leachet, garbage, batik.